AGENCY PROBLEM DALAM PENERAPAN PEMBIAYAAN AKAD MUDHARABAH PADA PERBANKAN SYARIAH - Aswadi Lubis (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2016)
The purpose of writing this article is to describe the agency problems that arise in the application of the financing with mudharabah on Islamic banking. In this article the author describes the use of the theory of financing, asymetri information, agency problems inside of financing. The conclusion of this article is that the financing is asymmetric information problems will arise, both adverse selection and moral hazard. The high risk of prospective managers (mudharib) for their moral hazard and lack of readiness of human resources in Islamic banking is among the factors that make the composition of the distribution of funds to the public more in the form of financing. The limitations that can be done to optimize this financing is among other things; owners of capital supervision (monitoring) and the customers themselves place restrictions on its actions (bonding).